2014
DOI: 10.1007/s13399-014-0122-x
|View full text |Cite
|
Sign up to set email alerts
|

Ash reduction of corn stover by mild hydrothermal preprocessing

Abstract: Lignocellulosic biomass such as corn stover can contain high ash content, which may act as an inhibitor in downstream conversion processes. Most of the structural ash in biomass is located in the cross-linked structure of lignin, which is mildly reactive in basic solutions. Four organic acids (formic, oxalic, tartaric, and citric) were evaluated for effectiveness in ash reduction, with limited success. Because of sodium citrate's chelating and basic characteristics, it is effective in ash removal. More than 75… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 19 publications
(36 citation statements)
references
References 26 publications
0
35
1
Order By: Relevance
“…Specific chemical pretreatments include steam, liquid water, acids, bases, ionic liquids [108], organosolv [109], sulfite pretreatment (SPORL) [110,111], and ammonia fiber explosion (AFEX) [112]. Chelating agents like sodium citrate effectively remove ash from corn stover under mild hydrothermal pretreatment [32]. These chemical pretreatments can be strongly influenced by processing parameters.…”
Section: Chemical Physical and Thermal Pretreatments Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Specific chemical pretreatments include steam, liquid water, acids, bases, ionic liquids [108], organosolv [109], sulfite pretreatment (SPORL) [110,111], and ammonia fiber explosion (AFEX) [112]. Chelating agents like sodium citrate effectively remove ash from corn stover under mild hydrothermal pretreatment [32]. These chemical pretreatments can be strongly influenced by processing parameters.…”
Section: Chemical Physical and Thermal Pretreatments Methodsmentioning
confidence: 99%
“…As a pretreatment process, mild hydrothermal treatment reduces ash content when used in combination with a sodium citrate chelating agent [32]. This could have potential benefits when processing biomass for further conversion processes that require low ash content.…”
Section: Hydrothermal Liquefactionmentioning
confidence: 99%
“…A variety of acid washes have been studied to elucidate their ability to decrease feedstock ash content. The addition of strong acids such as nitric, sulfuric, and hydrochloric acid, as well as weak acids such as hydrofluoric, phosphoric, oxalic, nitric, and acetic acid to wash greatly decreases biomass ash content [17,[19][20][21][22][23][24][25][26]. However, these treatments generate a waste stream that must be neutralized.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, common chelating agents typically have a buffering effect, and therefore pH-dependent hydrolysis of cellulose and hemicellulose would be negligible. In fact, Reza et al [26] recently described a mild hydrothermal preprocessing technology that reduces the ash content of dry corn stover by 77% using sodium citrate, a common industrial chelating agent. This process was shown to have no effect on the holocellulose fraction, although an increase in Na ion concentration was noted due to the presence of this ion in the chelating agent (up to 3 moles Na per mole of citrate ion).…”
Section: Introductionmentioning
confidence: 99%
“…Nitric acid removed the most inorganics at the lowest concentration; however, acetic acid removed the most inorganics at the same pH level. Reza et al [22] reported removal of inorganics from corn stover using formic, oxalic, tartaric, and citric acids, finding that the 5 % sodium citrate at 130°C and 2.7 bar removed 86 % of combined Na, Mg, K, and Ca because of its chelating properties.…”
Section: Introductionmentioning
confidence: 99%